2011
DOI: 10.4267/2042/37719
|View full text |Cite
|
Sign up to set email alerts
|

COL1A1 (collagen, type I, alpha 1)

Abstract: This work is licensed under a Creative Commons Attribution-Noncommercial-No Derivative Works 2.0 France Licence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…COL1A1, located in chromosome 17, region 17q21–22, and presenting 51 exons, encodes the pro-α1 chain of type I collagen, which is consisting of a triple helix composed of one α2 chain and two α1 chains [ 36 ]. A fibrillar collagen C‑terminal domain (COLF) a collagen triple‑helix repeat and A von Willebrand factor type C (vWFC) domain are three conservative domains of COL1A1 [ 37 ]. Previous studies have shown that the expression of COL1A1 is correlated to a variety of tumor types, and COL1A1 is highly expressed in tumor tissues and cells [ 38 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…COL1A1, located in chromosome 17, region 17q21–22, and presenting 51 exons, encodes the pro-α1 chain of type I collagen, which is consisting of a triple helix composed of one α2 chain and two α1 chains [ 36 ]. A fibrillar collagen C‑terminal domain (COLF) a collagen triple‑helix repeat and A von Willebrand factor type C (vWFC) domain are three conservative domains of COL1A1 [ 37 ]. Previous studies have shown that the expression of COL1A1 is correlated to a variety of tumor types, and COL1A1 is highly expressed in tumor tissues and cells [ 38 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Collagen type I α 1 (COL1A1) encodes the pro-α 1 chains of type I collagen, which has a triple helix composed of two α 1 chains and one α 2 chain ( 2 ). COL1A1 contains three conservative domains, namely a von Willebrand factor type C (vWFC) domain, a collagen triple-helix repeat and a fibrillar collagen C-terminal domain (COLF) ( 3 ). It was recently found that COL1A1 is associated with a variety of tumor types, and that the expression of COL1A1 was high in tumor tissues and cells ( 4 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Type I collagen is a product of two genes. COL1A1, 1 which is located in chromosome 17, encodes pro α 1 (I) protein chain and COL1A2, 2 located in chromosome 7, encodes pro α 2 (I) chain. Its precursor form, type I procollagen, is synthesized by fibroblasts in soft tissues and by osteoblasts in bone tissue, and it contains aminoterminal and carboxyterminal propeptides.…”
Section: Introductionmentioning
confidence: 99%